The relationship between emotional intelligence and employee motivation among support staff at Universiti Malaysia Sarawak (UNIMAS) / Muhammad Asyraf Ahmad Fadli - Ahmad Fadli, Muhammad Asyraf (2017)
Organizations should consider emotional intelligence as an important aspect for them to increase the success of the organizations in achieving higher goals through their employees’ motivation. The purpose of this study is to investigate the relationship between emotional intelligence (EI) and employee motivation. Previous studies have been focused more on Middle East organization which resulted in lack of literature in setting place and environment of Malaysia. Data were collected using Emotional Intelligence and Employee Motivation Questionnaire with Cronbach’s alpha of 0.842 and 0.628 respectively and was analyse using IBM SPSS v23. This study used convenience sampling and 108 individuals support staff were chosen from 3 departments (Administration, Human Resource and Finance). The results show a significant correlation between emotional intelligence along with its subset, including self-awareness, self-management, social awareness and relationship management with the motivation of the employees in UNIMAS.